The Enhancing Elementary Students’ Conceptual Understanding of Ecosystems through a Metaverse-Based Project-Based Learning Model: A Quasi-Experimental Study - Candra Abdillah; Erni Suharini; Arif Widiyatmoko; Barokah Isdaryanti (Jurnal Elementaria Edukasia, 2026)
This study aims to analyze the effectiveness of the metaverse-based PjBL model on elementary school students' conceptual understanding of the Natural and Social Sciences subject of Ecosystem material. This study uses a quantitative approach and quasi-experimental methodology with a times series design. The research sample is fifth grade students in Banten, Indonesia. This sample selection uses a simple random sampling technique. The data collection technique in this study uses a test technique with a concept understanding test instrument. The data analysis technique uses a one-sample t-test, one-sample binomial test, N-gain test, and paired sample t-test. The results of the study include: (1) The average conceptual understanding of students after being taught with the metaverse-based PjBL model is 83.70; (2) the classical completeness of students' conceptual understanding after being taught with the metaverse-based PjBL model is 76.67%; (3) there is an increase in students' conceptual understanding after being taught with the metaverse-based PjBL model with a moderate increase criterion of 63.33%, (4) there is a significant difference in students' conceptual understanding before learning with an average of 58.30 and after learning with an average of 83.70 so that there is a difference in scores of 25.40. The conclusion of this study is that the metaverse-based PjBL model is effective in increasing elementary school students' conceptual understanding of the Natural and Social Sciences subject of the Ecosystem material.